2022
DOI: 10.3390/bioengineering9010015
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Effects of 3D Resins Used in Orthodontics: A Systematic Review

Abstract: Three-dimensional (3D) resin medical-dental devices have been increasingly used in recent years after the emergence of digital technologies. In Orthodontics, therapies with aligners have gained popularity, mainly due to the aggressive promotion policies developed by the industry. However, their systemic effects are largely unknown, with few studies evaluating the systemic toxicity of these materials. The release of bisphenol A and other residual monomers have cytotoxic, genotoxic, and estrogenic effects. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…A systematic review investigating the biological effects of 3D-printed resins used in orthodontics concludes that 3D-printed aligners exhibit higher levels of cytotoxicity and genotoxicity than thermoplastic resins, especially if they have not been subjected to a final surface treatment. This prompts the clinician to act with caution, especially when treating young children and growing patients in order to protect them from fertility issues [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review investigating the biological effects of 3D-printed resins used in orthodontics concludes that 3D-printed aligners exhibit higher levels of cytotoxicity and genotoxicity than thermoplastic resins, especially if they have not been subjected to a final surface treatment. This prompts the clinician to act with caution, especially when treating young children and growing patients in order to protect them from fertility issues [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the biological effects of 3D resins used in clear aligners or retainers also reveals that the evidence of the release of bisphenol A and other monomers, either in vitro or clinical studies, remains ambiguous due to few robust results in the current literature. There is an absolute need for further studies in these domains, especially given the possible implications for the fertility of young patients [ 112 ].…”
Section: Properties Of Clear Aligner Materialsmentioning
confidence: 99%
“…Harouny et al demonstrated that the use of phosphoric acid on the lithium disilicate surface provide efficient cleaning [34]. Therefore, the main aim of studies in the dental restoration field is to ameliorate the mechanical properties, bond strength, and durability of direct and indirect restoration approaches, as well as to improve the techniques used to bond brackets to teeth with different restorative materials in orthodontic treatments [35,36].…”
Section: Final Restoration Materials and Preparation Stepsmentioning
confidence: 99%